Perchloroethylene: acute occupational poisoning and a proposal for its replacement with other less toxic substances - Pere Sanz-Gallen; Albert Sanz-Ribas; Gabriel Martí-Amengual; Jaime Fernández-Colomé (Nofer Institute of Occupational Medicine, 2019)
Perchloroethylene is used mainly as a solvent in dry cleaning, cleaning of electrical equipment, and degreasing of metal parts. The authors report a case of acute poisoning with perchloroethylene contracted by a maintenance worker when cleaning an electric transformer. Since perchloroethylene may cause severe poisoning and the International Agency for Research on Cancer has classified it as a probable carcinogen for humans, the authors have revised the main substances that may replace perchloroethylene in the workplace. Med Pr. 2019;70(3):393-5